Strategy of the National Movement to Save Natural Resources in Structuring Palm Oil Licensing in Indonesia - Sulistyanto Sulistyanto; Bambang Giyanto; Ratri Istania (International Journal of Economics Development Research (IJEDR), 2023)
This study analyzes the implementation of the GNPSDA Program in structuring oil palm plantation licensing in Indonesia using the Grindle approach and adding two exogenous variables from the Institutional Analysis Development (IAD) approach. Through a qualitative approach, researchers explore information from various key informants, document review and spatial data review to find factors that affect the implementation of the GNPSDA program and formulate future GNPSDA strategy improvements. The research findings state that all policy content variables including interest affected; type of benefit; extent of change envisioned; site of decision making; program implementors; and resources committed and implementation context variables including power, interest, and strategy of actors involved; institutions and regime characteristics; compliance and responsiveness as well as two IAD variables namely biophysical characteristics of palm oil and community attributes affect the implementation of the GNPSDA Program. In addition, the study also found that the variables influence each other. However, due to limitations, this study did not conduct causality analysis between variables. The research suggests that the KPK and the Ministry of Agriculture should be able to adopt the formulation of the GNPSDA strategy as an effort to improve governance and prevent corruption in the palm oil licensing sector in the future. In addition, for future research development, it is necessary to do tracing between variables to identify causal relationships between variables so that in-depth analysis is obtained.